Safety, Tolerability and Immunogenicity of Pentavalent Rotavirus Vaccine Manufactured by a Modified Process. Issue 4 (April 2017) - Martinón-Torres, Federico; Greenberg, David; Varman, Meera; Killar, John A.; Hille, Darcy; Strable, Erica L.; Stek, Jon E.; Kaplan, Susan S.
Abstract : Background: Rotavirus is the leading cause of severe diarrhea in infants and young children. The current formulation of pentavalent rotavirus vaccine (RV5) must be stored refrigerated at 2–8°C. A modified formulation of RV5 (RV5mp ) has been developed with stability at 37°C for 7 days and an expiry extended to 36 months when stored at 2–8°C. Methods: This study (ClinicalTrials.gov identifier: NCT01600092; EudraCT number: 2012-001611-23) evaluated the safety, tolerability and immunogenicity of RV5mp versus the currently marketed RV5 in infants. To maintain blinding, both vaccine formulations were stored refrigerated at 2–8°C for the duration of the study. Immunogenicity endpoints were (1) serum neutralizing antibody titers to human rotavirus serotypes G1, G2, G3, G4 and P1A[8] and (2) proportion of subjects with a ≥3-fold rise from baseline for serum neutralizing antibody to human rotavirus serotypes G1, G2, G3, G4 and P1A[8] and serum antirotavirus immunoglobulin A. Results: The RV5mp group (n = 505) and RV5 group (n = 509) had comparable safety profiles. There were no deaths and no vaccine-related serious adverse events in this study. With respect to immunogenicity, RV5mp was noninferior compared with RV5. Serum neutralizing antibody responses by country and breast-feeding status were generally consistent with the overall results. Conclusions: RV5mp enhances storage requirements while maintaining the immunogenicity and safety profile of the currently licensed RV5. A vaccine that is stable at room temperature may be more convenient for vaccinators, particularly in places where the cold chain is unreliable, and ultimately will permit more widespread use. Abstract : Supplemental Digital Content is available in the text.